Editorial: Políticas públicas y educación - Horacio Salvador-Hernández (EDUNEXA, 2026)
Educational public policies constitute a strategic component for guiding the transformation of education systems and responding to the challenges associated with quality, equity, financing, inclusion, and institutional innovation. This issue of EDUNEXA, Journal of Educational Research, Volume 3, Number 3, corresponding to the year 2026, dedicated to “Public Policies and Education,” brings together six contributions that examine complementary dimensions of public action in education. The works address Latin American educational reforms, sustainable financing of higher education, the right to education, quality assurance policies, decentralization with a territorial focus, and evaluation through indicators. Taken together, the research allows us to understand that an effective educational policy requires coordination among the State, institutions, communities, and educational stakeholders, based on evidence, participation, social justice, and systematic evaluation mechanisms to guarantee sustainable transformations.